A comparative review of current international atrial fibrillation guidelines from a primary care perspective - Jazlan Jamaluddin; Siok Fuang Liong; Hooi Chin Beh; Karleen Chong; Jin Ian Choong; Ahmad Firdaus Zakaria; Nik Aminah Nik Abdul Kadir (Malaysian Family Physician)
Atrial fibrillation (AF) is the most frequent sustained arrhythmia globally with significant morbidity and mortality. A local guideline has been created to help physicians in clinical decision-making by outlining various generally accepted approaches for the diagnosis, management and prevention of AF. This guideline was published 10 years ago, and it is imperative that new guidelines based on the latest consensus be renewed. Since then, various clinical guidelines have been issued in the past 5 years to standardise the management of AF, including the American College of Cardiology, European Society of Cardiology, National Institute for Health and Care Excellence and Asia Pacific Heart Rhythm Society guidelines. This review aims to provide a comprehensive comparison of these guidelines across multiple aspects of clinical management, including management frameworks, screening, anticoagulation, stroke and bleeding risk assessments, rate and rhythm control, follow-up, comorbidity management and technology usage.